Clinical Burden and Healthcare Resource Utilization Associated With Managing Transfusion-dependent β-Thalassemia in England - Udeze, Chuka; Ly, Nelly F.; Ingleby, Fiona C.; Fleming, Sophia D.; Conner, Sarah C.; Howard, Jo; Li, Nanxin; Shah, Farrukh (Clinical therapeutics, 2025)
•Endocrine complications are common in transfusion-dependent β-thalassemia.•Use of healthcare resources is high in transfusion-dependent β-thalassemia compared to matched general population controls.•Patients received a mean of 13.62 red blood cell transfusions per year. Patients with transfusion-dependent β-thalassemia (TDT) have reduced levels of β-globin, leading to ineffective erythropoiesis and iron overload. Patients with TDT depend on regular red blood cell transfusions (RBCTs) and iron chelation therapy for survival and management of disease- and treatment-related clinical complications. This study describes the clinical and economic burden in patients with TDT in England. This longitudinal, retrospective study linked the Clinical Practice Research Datalink (CPRD) database with secondary care data from the Hospital Episode Statistics database to identify patients with a diagnosis of β-thalassemia between July 1, 2008, and June 30, 2018. Included patients had a diagnosis of β-thalassemia prior to the index date, ≥8 RBCTs per year for ≥2 consecutive years, and ≥1 year of follow-up data available from the index date. Each eligible patient was exact matched with up to 5 controls in the CPRD. Proportions of deaths and rates of mortality, acute and chronic complications, and healthcare resource utilization (HCRU) were calculated during the follow-up period. Of 11,359 identified patients with β-thalassemia, 237 patients with TDT met the eligibility criteria and were matched with 1184 controls. The mean age at the index date was approximately 25 years in the patient and control groups. The proportion of deaths (7.17% vs 1.18%; P < 0.05) and mortality rate (1.19 deaths per 100 person-years vs 0.20 deaths per 100 person-years) were higher among patients with TDT compared to controls. Endocrine complications and bone disorders were the most prevalent complications among patients with TDT (58.23%) and included osteoporosis (29.11%), diabetes mellitus (28.27%), and hypopituitarism (28.27%). Patients with TDT had a mean of 13.62 RBCTs per patient per year (PPPY). HCRU was substantially higher among patients with TDT, wherein patients with TDT had higher rates of prescriptions recorded in primary care (24.09 vs 8.61 PPPY), outpatient visits (16.69 vs 1.31 PPPY), and inpatient hospitalizations (17.41 vs 0.24 PPPY) than controls. Inpatient hospitalizations were primarily <1 day, with 16.62 events PPPY lasting <1 day and 0.79 events PPPY lasting ≥1 day. Patients with TDT aged ≥18 years had increased rates of mortality, clinical complications, and HCRU than those aged <18 years. Patients with TDT in England have higher mortality than matched controls, substantial disease-related clinical complications, and substantial HCRU. High mortality and clinical complications highlight the need for additional innovative therapies for TDT.